PEMBERDAYAAN INDUSTRI KECIL PERMEN KELAPA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT (Studi Kasus di Desa Mekar Sari Kecamatan Deli Tua Kabupaten Deli Serdang Provinsi Sumatera Utara) - Mulyana Mulyana; Rinaldi Tri Syahputra Nasution (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2019)
Empowerment of Small Coconut Candy Industry in Improving Community Welfare. This study aims to find out an overview of how to empower the coconut candy small industry as well as the supporting factors and inhibiting factors of the coconut candy small industry in Deli Tua Subdistrict. The research method used is descriptive qualitative with inductive approach. Data was collected by observation, interview, and documentation techniques. Analysis was carried out by data reduction, data presentation, triangulation, ang conclusion drawing. Based on the observations that have been made, the empowerment of the small coconut candy industry has been going well but not yet maximally, because of the inhibiting factors namely limited business insight, low technology insight, lack of awareness of entrepreneurs on the empowerment program given by the Deli Serdang Regency. To overcome obstacles, there are a number of suggestions that might be considered, namely: increasing marketing by promoting small coconut candy industries, increasing business insight, skills, and providing management training. Keywords: empowerment, small industry, society